A little leak goes a long way! 5‐Year‐outcome after transcatheter aortic valve implantation. Issue 5 (27th April 2022) - Inci, Errol; Block, Peter C
Abstract: Mild paravalvular leak after TAVR is associated with increased 5‐year mortality. Current noninvasive and invasive prediction models for mortality may only hold for short term outcomes. Other imaging modalities aside from transthoracic echocardiography should be strongly considered when assessing paravalvular leak, regardless of severity